Organization and distribution of repetitive DNA classes in the Cichla kelberi and Cichla piquiti genome - De Freitas Mourão, Andrea Abrigato [UNESP]; Daniel, Sandro Natal [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Ferreira, Daniela Cristina; Porto-Foresti, Fábio [UNESP] (International Society of Cytology, 2017)
The family Cichlidae is considered a non-Ostariophysi freshwater fish family with diverse and geographical distribution wide in the world; nevertheless there is scarce cytogenetic information for the group. Accordingly, we aim to characterize Cichla kelberi and Cichla piquiti specimens by conventional cytogenetic (Giemsa, Ag-NOR, Banding C) and cyto-molecular (FISH with 5S, 18S, Rag1, Rex3, Rex6 and telomeric probes) markers. In both species, cytogenetic analyses showed 2n=48 chromosomes (all of the subtelocentric/acrocentric type), NORs located terminally on the second chromosome pair and heterochromatic blocks in the centromeres of some chromosomes. The location of the 18S ribosomal gene confirms what was previously observed with impregnation with silver nitrate, while the 5S rDNA is in interstitial position on the third chromosome pair. The telomeric probe, as expected, was present only in telomeric regions of all chromosomes. The Rag1, transposable elements, Rex3 and Rex6 present dispersed sites throughout most of the chromosomes, not characterizing a definite pattern of distribution. Thus, the present study adds relevant information about the cytogenetics and behavior of different repetitive DNA families in C. kelberi and C. piquiti, which require future studies to understand the gene behavior and evolution in Neotropical fish, especially in the genus Cichla.
Keywords: Cichla kelberi; Cichla piquiti; Neotropical fish; Ribosomal gene; Transposable element